2007
DOI: 10.4028/www.scientific.net/kem.353-358.1879
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Oxidation Property of SUS304 by Gas Barrier Coating

Abstract: Stainless steel is widely used as a corrosion-resistant material. However, stainless steel corrodes at high temperature (573 K ~) due to the oxidization and grain boundary corrosion. To delay the oxidation at high temperature, coating of gas barrier film will be useful method. The purpose of this study is to improve the corrosion-resistant of SUS304 at high temperature by coating transparent SiOxNy film which has gas barrier properties. In addition, the influence of inlet gas mass flow rate ratio (N2/Ar+N2) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Measurement of film thickness and surface observations were performed using a stainless steel substrate because it was difficult for the PET substrate to be fixed accurately and flat on a stage for high magnification observations. However, we compared the OTR of the SiO x N y /PET sample and the oxidation behavior of the SiO x N y /stainless steel sample in our previous work and confirmed that they showed good agreement [24]. A Fourier-transform infrared spectroscope (Nicolet 380, Thermo ELECTRON Corp., Japan) was used to analyze the chemical bonds of the SiO x N y films.…”
Section: Methodsmentioning
confidence: 55%
“…Measurement of film thickness and surface observations were performed using a stainless steel substrate because it was difficult for the PET substrate to be fixed accurately and flat on a stage for high magnification observations. However, we compared the OTR of the SiO x N y /PET sample and the oxidation behavior of the SiO x N y /stainless steel sample in our previous work and confirmed that they showed good agreement [24]. A Fourier-transform infrared spectroscope (Nicolet 380, Thermo ELECTRON Corp., Japan) was used to analyze the chemical bonds of the SiO x N y films.…”
Section: Methodsmentioning
confidence: 55%